Pelaksanaan Supervisi Imunisasi Campak di Puskesmas Wilayah Surabaya Utara - Dian Febrina Anggraini; Ratna Dwi Wulandari (Universitas Airlangga, 2016)
Measles is one of endemic diseases in East Java especially in north Surabaya, the home of specific ethnic which resist of immunization. Surabaya District Health Office targeted their Measles immunization is above 90%,but unfortunately this target are never been reached. The purpose of this study was to analyze the management process of immunization program, especially the supervision. The guidance of supervision is regulated in HealthMinister Regulation number 42, on 2013. Supervision is involved performance standard setting, monitoring and corrective action. This is a quantitative study with descriptive and cross sectional design. The sampling wascalculated by using simple random sampling. The interviews through open and close question were conducted to 38 Managers of Immunization program in Public Health Centre. The result showed that the implementation ofsupervision has implemented by guidance the supervision of immunization programme. The study showed that only 2.63% or just one of Public Health Centre has already supervised by District Health Office and 5.26% or twoPublic Health Centres has supervised three times and suit with guidance implementation of general supervision. From this study, it is important for District Health Office to add new person as Supervisor and Public HealthCentres and ensure that its supervision follow the supervision guidance.Keywords: Measles immunization, North Surabaya, supervision